Observations on the growth and survival of Nipa (Nypa fruticans Wurmb) seedlings under different salinity concentrations - Alcala, Marilyn T. (2007)
The primary objective of this study was to determine the effects of salinity on the growth and morphology of the nipa palm (Nypa fruticans). The field study was done in Binicuil, Kabankalan, Negros Occidental, in the months of January to October 2007. Six plots each measuring 10m x 10m and separated from each other for 100m were observed during this period of time. The physico-chemical parameters measured were soil and water salinity, soil and water pH, and soil texture. Laboratory experiment on nipa seedlings was also conducted for 34 weeks to observe the effects of salinity on the growth of nipa seedlings. In the field, the mature nipa palms in the six plots showed variations in morphological characteristics, but these variations were not significant. The results of the field survey showed that most seedlings were found in plots with 30-42 ppt salinity. The results in the field are confirmed by the experimental results showing that the growth was fastest at 0 ppt salinity in terms of the increase in the number and length of petioles, leaves, and roots. The growth of yougn seedlings of Nipa palms appears to be most rapid at salinities much lower than 30 ppy., especially 0-15 ppt. It is recommended that nipa farmers plant nipa at lower salinities in silty to sandy loam soils.
Keywords: Nypa palm; Salinity